2000
DOI: 10.1086/309011
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Evolution of the Envelopes of Deeply Embedded Massive Young Stars

Abstract: The physical structure of the envelopes around a sample of fourteen massive young stars is investigated using maps and spectra in submillimeter continuum and lines of C 17 O, CS, C 34 S and H 2 CO. Nine of the sources are highly embedded luminous (10 3 − 10 5 L ⊙ ) young stellar objects which are bright near-infrared sources, but weak in radio continuum; the other objects are similar but not bright in the near-infrared, and contain "hot core"-type objects and/or ultracompact H II regions. The data are used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
354
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(411 citation statements)
references
References 114 publications
(134 reference statements)
54
354
3
Order By: Relevance
“…3 for b = 5 km s −1 , shows that emission starts filling in the absorption significantly for T ex > ∼ 250 K. The resulting column densities are a factor of ∼3-6 higher than in the case of pure absorption. Van der Tak et al (2000b) and Mueller et al (2002) have shown that temperature and density gradients are present in the envelopes of the massive protostars studied here. Adopting the physical structure from van der Tak et al (2000b) and assuming a Boltzmann distribution in each shell with T ex equal to the dust temperature in that shell increases the inferred column density by similar factors as in the case of a constant temperature and density.…”
Section: Radiative Transfer Effectsmentioning
confidence: 59%
See 2 more Smart Citations
“…3 for b = 5 km s −1 , shows that emission starts filling in the absorption significantly for T ex > ∼ 250 K. The resulting column densities are a factor of ∼3-6 higher than in the case of pure absorption. Van der Tak et al (2000b) and Mueller et al (2002) have shown that temperature and density gradients are present in the envelopes of the massive protostars studied here. Adopting the physical structure from van der Tak et al (2000b) and assuming a Boltzmann distribution in each shell with T ex equal to the dust temperature in that shell increases the inferred column density by similar factors as in the case of a constant temperature and density.…”
Section: Radiative Transfer Effectsmentioning
confidence: 59%
“…The effect of emission filling in the absorption is discussed in Sect 4. In Paper II it will be shown that combining the inferred temperature and density gradients from van der Tak et al (2000b) with a detailed chemical model, results in H 2 O abundances of ∼10 −4 in the warm gas and can successfully explain the observed ro-vibrational spectrum of gasphase H 2 O. Therefore, the difference between the gas-phase H 2 O abundance in the warmest source and the ice abundance in the coldest source is probably due to both the assumption of pure absorption and of a homogeneous source with a constant excitation temperature and column density in the current models.…”
Section: Abundancesmentioning
confidence: 99%
See 1 more Smart Citation
“…For HCN, rotational transitions in the submillimeter and ro-vibrational transitions in the infrared can be observed. In a number of massive YSOs the HCN abundance derived from submillimeter observations is a factor of ∼100 lower than that derived from infrared observations, suggesting a jump in its abundance in high temperature regions van der Tak et al 1999van der Tak et al , 2000Boonman et al 2001). There is still considerable debate whether such abundance jumps are mainly due to evaporation of ices, to quiescent high-temperature chemistry at a few hundred K or to shock chemistry at a few thousand K. The comparison of the Orion IRc2 and the shocked Peak 1 and Peak 2 results can provide constraints on the different models.…”
Section: Introductionmentioning
confidence: 94%
“…b CO column density and CO/H 2 ratio from van der Tak et al (2000). c CR rate from van der Tak & van Dishoeck (2000).…”
Section: Comparison With Observationsmentioning
confidence: 99%